2005
DOI: 10.1007/s11284-005-0111-4
|View full text |Cite
|
Sign up to set email alerts
|

Survival and cause‐specific mortality rates of female sika deer in eastern Hokkaido, Japan

Abstract: Survival and cause-specific mortality rates of female sika deer (Cervus nippon) were studied using radio telemetry in eastern Hokkaido, Japan. We captured and radio-collared 18 female deer, and monitored their survival from April 1993 to May 1996. Estimated annual survival rate for adult females was 0.779 (95% confidence interval was 0.609-0.997). The harvest mortality rate of adult females was higher than the natural mortality rate. Experimental female hunting during 1994-1996 contributed to an increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In eastern Hokkaido, occasional predation and scavenging by the brown bear Ursus arctos yesoensis is observed. Although recent research on cause‐specific mortality rates of the eastern Hokkaido sika deer showed that harvesting mortality was higher than natural mortality (Uno & Kaji, 2006), severe winters and resulting food scarcity are the dominant source of natural mortality in the northern populations (Takatsuki, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…In eastern Hokkaido, occasional predation and scavenging by the brown bear Ursus arctos yesoensis is observed. Although recent research on cause‐specific mortality rates of the eastern Hokkaido sika deer showed that harvesting mortality was higher than natural mortality (Uno & Kaji, 2006), severe winters and resulting food scarcity are the dominant source of natural mortality in the northern populations (Takatsuki, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The individuals may inhabit the wetland to avoid hunting risk ( Lone et al, 2015 ) as the majority of this area is a Wildlife Protection Area, which could allow these individuals to continue to increase until reaching the carrying capacity of the wetland. After the extinction of the gray wolf around 1890 ( Inukai, 1933 ) in Hokkaido, the main cause of deer mortality in eastern Hokkaido has primarily been harvest by hunters with adult female mortality rates estimated at 0.118 (harvest) and 0.053 (natural) ( Uno & Kaji, 2006 ). Furthermore, movements of some Takkobu individuals that exhibited atypical movements, such as leaving the wetland for surrounding areas and establishing new home ranges there, indicated that Kushiro Wetland may be a population source in eastern Hokkaido.…”
Section: Discussionmentioning
confidence: 99%
“…and from 1 November to 28 February in the fiscal year 2000. We analyzed relationships using a model II regression analysis using spotlight count data as the independent variable, and data from aerial surveys, CPUE, SPUE, and cost of damage as dependent variables (Sokal and Rohlf 1995). We used the major axis method and estimated the slope of dependent variables on the independent variable using JMP 5.1.1 (SAS Institute, Cary, N.C.).…”
Section: Hunting Datamentioning
confidence: 99%
“…The estimation and evaluation of population sizes and trends is essential for conserving and managing wildlife populations (Begon et al 1996;Thompson et al 1998). However, the real absolute size of wildlife populations is often unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation